4-Thiobenzoic acid-functionalized nanocomposite probes for surface-enhanced raman spectroscopy-based detection of CA19-9 in colorectal adenocarcinoma - Yinan Hu; Tao Liu; Bo Guo; Miao Ni; Yanrong Li (Alexandria Engineering Journal)
This study presents a novel surface-enhanced Raman spectroscopy (SERS) method for detecting CA19–9 in colorectal adenocarcinoma using 4-thiobenzoic acid (4-TBA) functionalized gold nanoparticles (nanospheres). The optimized SERS probes exhibited a maximum enhancement at pH 7 and 50 μM 4-TBA concentration, with stable signal achieved after 2 hours of incubation. The assay demonstrated a wide dynamic range of 1–100 U/mL, with a lower limit of quantification of 1.0 U/mL. Excellent selectivity was observed against common serum interferents, with normalized SERS intensities within 10 % of CA19–9 alone. Recovery studies in spiked serum samples yielded results ranging from 94.5 % to 105.2 %, indicating minimal matrix effects. Clinical validation using 70 serum samples (50 colorectal adenocarcinoma patients, 20 healthy volunteers) showed strong agreement with a commercial ELISA kit (Pearson's r = 0.987, p < 0.0001). Bland-Altman analysis revealed a mean bias of −0.37 U/mL between SERS and ELISA methods. The SERS-based approach offers advantages including rapid analysis (<1 hour), small sample volume requirements (5–10 μL), and potential for multiplexing. This method shows promise for early detection, disease monitoring, and treatment response evaluation in colorectal adenocarcinoma, with potential applications in both clinical and research settings.